2016
DOI: 10.1117/1.jbo.21.10.101410
|View full text |Cite
|
Sign up to set email alerts
|

Blood-pressure-induced oscillations of deoxy- and oxyhemoglobin concentrations are in-phase in the healthy breast and out-of-phase in the healthy brain

Abstract: Abstract. We present a near-infrared spectroscopy (NIRS) study of local hemodynamics in the breast and the brain (prefrontal cortex) of healthy volunteers in a protocol involving periodic perturbations to the systemic arterial blood pressure. These periodic perturbations were achieved by cyclic inflation (to a pressure of 200 mmHg) and deflation (at frequencies of 0.046, 0.056, 0.063, 0.071, and 0.083 Hz) of two pneumatic cuffs wrapped around the subject's thighs. As a result of these systemic perturbations, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…On the other hand, we assume the constant phase shift to be 0 if blood volume oscillations are dominant, as has been suggested previously. 14,15 Although blood flow oscillations are usually dominant in brain tissue, 28 a mixture of both blood flow and blood volume oscillations may be present, as has been previously reported in the literature, which may result in a constant phase difference in between 0 and 180 . 29,30 Figure 1 illustrates these effects on simulated data.…”
Section: Cerebral Autoregulation Analysis Without Tt-bf/bv Correctionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, we assume the constant phase shift to be 0 if blood volume oscillations are dominant, as has been suggested previously. 14,15 Although blood flow oscillations are usually dominant in brain tissue, 28 a mixture of both blood flow and blood volume oscillations may be present, as has been previously reported in the literature, which may result in a constant phase difference in between 0 and 180 . 29,30 Figure 1 illustrates these effects on simulated data.…”
Section: Cerebral Autoregulation Analysis Without Tt-bf/bv Correctionmentioning
confidence: 76%
“…Furthermore, the OxyHb-HHb phase difference spectrum during REST and DB was compatible with dominance of blood flow oscillations, which is typical for brain tissue and atypical for extracranial tissue. 28 NIRS is also a focal measurement and since we only measured in the MCA territory, we cannot generalise our findings to other vascular territories, which precludes investigation of regional heterogeneity of cerebral autoregulation. Finally, the reproducibility of the findings has not yet been established, and longer measurements may be needed to evaluate if the NIRS-based autoregulation estimates and transit time and blood flow/volume estimates are stable over time and react similarly to repeated challenges.…”
Section: Limitationsmentioning
confidence: 98%
“…The data for nine of the female subjects (nn. 13–21) have been previously analyzed for a comparison of the relative phase and amplitude of oxyhemoglobin and deoxyhemoglobin concentration oscillations in brain and breast tissue [29].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, associated 77 sLFOs in blood flow and velocity have been found (Killip, 1962;Fagrell et al, 1977) and, 78 later, transcranial Doppler ultrasonography and optical methods confirmed their traces 79 within the brain (Giller et al, 1999;Obrig et al, 2000). This optically detected sLFO was 80 found in both oxy-and deoxy-Hb with an interesting phase difference exclusively observed 81 in the brain (Rayshubskiy et al, 2014;Tgavalekos et al, 2016). Additionally, sLFOs were 82 found in electroencephalographic recordings, for which arterial vasomotion was suggested 83 as the origin (Nikulin et al, 2014), although it is unclear how the vasomotion accounts for 84 the fMRI signal mainly from the capillary bed.…”
mentioning
confidence: 90%